2000
DOI: 10.3406/paleo.2000.4708
|View full text |Cite
|
Sign up to set email alerts
|

Feu et archéoanthropologie au Proche-Orient (épipaléolithique et néolithique). Le lien avec les pratiques funéraires. Données nouvelles de Çayönü (Turquie)

Abstract: Many burned skeletal remains have been found in the Çayönü Skull Building. The upper layer yielded 71 skulls and some post-cranial remains which might have been burned during the intentional burning of the building. In the earlier layer BM la, there were also many burned human remains. A burned bone deposit from this layer was studied using taphonomic approach so as to reconstruct the burial phases. It appears that the bones were selected prior to their deposit in the pit ; they were then broken in situ by nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…However, the deliberate treatment by fire of the remains at Tell el-Kherk is obvious considering the pyre structures and the number of skeletons involved. It should be distinguished from instances of accidental burning and all cases where the human remains are burned not as first intention (intentional destruction of the grave structure by fire, proximity to a fire place etc…[see for instance 13 ]). A few centuries later, during the 6 th millennium in Halaf contexts, cremation and pyre-pits are also documented in sites further to the east such as Yarim Tepe II [ 114 ] and further to the north-west at Mesrin [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the deliberate treatment by fire of the remains at Tell el-Kherk is obvious considering the pyre structures and the number of skeletons involved. It should be distinguished from instances of accidental burning and all cases where the human remains are burned not as first intention (intentional destruction of the grave structure by fire, proximity to a fire place etc…[see for instance 13 ]). A few centuries later, during the 6 th millennium in Halaf contexts, cremation and pyre-pits are also documented in sites further to the east such as Yarim Tepe II [ 114 ] and further to the north-west at Mesrin [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practice of cremation has also been mentioned several times for pre-ceramic periods in the Near East but often questioned, since accidental fire exposure cannot, in most instances, be ruled out. The presence of burnt isolated human bones is not exceptional but remains poorly understood due to the lack of accurate contextual and taphonomic studies [see synthesis in: 13 ]. It seems that fire was an integral part of funerary ceremonies as hearths were regularly situated close to, or were in association with graves at least from the beginning of sedentarization [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The house and outer courtyard were visited and activities took place involving the addition of ash and charcoal to the sediment. Although there is no evidence of human bones affected by fire at Tell Qarassa North, it has been suggested that fire was used in funerary rituals in the regional Pre-Pottery Neolithic, as at Çayönü and As ßıklı Höyük (LeMort et al, 2000). A quern in position to be used also suggests that some milling or grinding tasks were carried out inside the abandoned house, probably to prepare food.…”
Section: Funerary Rituals In An Abandoned Housementioning
confidence: 96%
“…Archaeological researches on the Neolithic settlements of Anatolia have revealed a high degree of variation and also a marked regional similarity in funerary practices (Mellaart, 1967;Ö zbek, 1988a,b, 2005aÖ zdogan and Ö zdogan, 1990;LeMort et al, 2000;Molleson et al, 2005). Even if there is no direct evidence that would elucidate the motives behind these various mortuary practices, they can still be considered among the conceptual changes surrounding life and death during this new cultural period known as the Neolithic.…”
Section: Introductionmentioning
confidence: 97%